MORAL DIMENSION IN INDONESIAN EDUCATION - Agustinus Wisnu Dewantara (Sean Institute, 2023)
Education is the central thing in human formation. The number of crimes involving educated people shows the importance of integrated morality education in the education system in Indonesia. Education is not enough to master the mastery of the material and is purely cognitive. Education must produce integral human beings, be it knowledge, attitudes, and morality. This paper seeks to explore the moral dimension of the education system. The research used studies from various texts and writings related to the theme of morality and education in Indonesia. Moral education has the consequence that humans need training to recognize the truth and the nature of their human abilities, namely free will, conscience, and reason. Education that includes morals makes it possible to synthesize students' consciences in the midst of life's problems that cannot only experience cognitive awareness.